Water Resources Management using Geographic Information Systems (G.I.S.): Case Study of the Nestos River Basin - Fytilis, Konstantinos (Journal of Multidisciplinary Research Advancements, 2025)
Directive 2000/60/EC introduces a framework for water protection by assessing ecological quality through biological, physicochemical, and hydromorphological parameters at the river basin level. Member States are required to maintain registers of water bodies used for human consumption, in compliance with Community legislation. This study aims to develop an electronic database (EDB) to document water supply drillings in accordance with the Directive, using Geographic Information Systems (GIS) for a pilot implementation in the Nestos River Basin. The EDB enables real-time monitoring and prompt intervention by authorities to address water quality issues, such as nitrate pollution, thereby supporting sustainable water resource management and public health protection.